School Operator Management at Mubarokul Ulum Brebes Middle School - Aji, Adilla Septi Rizqiana; Abdillah, Jujun Junaedi; Sopani, Midun; Romadhoni, Muhamad; Nurlaily, Siti; Sari, Yuni Melani (Multidiscience : Journal of Multidisciplinary Science, 2024)
This research aims to analyze the management of school operators at Mubarokul Ulum Middle School, Brebes, focusing on competencies, tasks, and challenges faced in supporting school administration in the digital era. This research uses a qualitative descriptive method with data collection techniques, including observation, interviews, and document analysis. The research results show that school operator management at Mubarokul Ulum Brebes Middle School is carried out through systematic planning, organizing, mobilizing, and controlling stages. At the planning stage, various parties, such as the principal, head of administration, and school operators, contribute to identifying goals, tasks, and required resources. A transparent organizational structure ensures the effectiveness of administrative management. The mobilization stage directs related parties to work according to their offline and online duties through the Dapodik application. Control is carried out by monitoring system access and use and ensuring regular data updates. However, there are several obstacles, such as technical problems with the Dapodik software, computer hardware damage, and school operators' low salaries, which affect their work efficiency and motivation. Therefore, solutions are needed to overcome technical problems and improve school operators' welfare to support school administration's smooth running in the digital era.